Impact of global warming on Chinese wheat productivity - You, Liangzhi; Rosegrant, Mark W.; Fang, Cheng; Wood, Stanley (International Food Policy Research Institute, 2005)
Climate change continues to have major impact on crop productivity all over the world. While many researchers have evaluated the possible impact of global warming on crop yields using mainly indirect crop simulation models, there are relatively few direct assessments on the impact of observed climate change on past crop yield and growth. We use a 1979-2000 Chinese crop-specific panel dataset to investigate the climate impact on Chinese wheat yield growth. We find that a 1 percent increase in wheat growing season temperature reduces wheat yields by about 0.3 percent. This negative impact is less severe than those reported in other regions. Rising temperature over the past two decades accounts for a 2.4 percent decline in wheat yields in China while the majority of the wheat yield growth, 75 percent, comes from increased use of physical inputs. We emphasize the necessity of including such major influencing factors as physical inputs into the crop yield-climate function in order to have an accurate estimation of climate impact on crop yields.